Positive Solutions for Systems of Nonlinear Higher Order Differential Equations with Integral Boundary Conditions - Yaohong Li; Xiaoyan Zhang (Abstract and Applied Analysis)
By constructing some general type conditions and using fixed point theorem of cone, this paper investigates the existence of at least one and at least two positive solutions for systems of nonlinear higher order differential equations with integral boundary conditions. As application, some examples are given.